Nonlinear Behaviour in Embi Series from Eastern Europe: Evidence of Window Size Effect - Gorigoitia-Gallardo, J (2014)
The main objective of this article is to explore how the number of observations included in a window may impact the rejection rate of linear windows. We employ two methodologies proposed in the literature in order to study the linear and nonlinear behaviour. We use daily Emerging Markets Bond Index (EMBI) index spreads from six of the most important Eastern European countries (Bulgaria, Hungry, Poland, Russia, Serbia and Ukraine). The empirical results show what we call window size effect because when we include more than 50 observations in each window, the rejection rate increases using the two different methodologies. Therefore, our findings support the idea that, even in this well informed and sophisticated market, the weak-form of the efficient market hypothesis cannot be confirmed. © 2013 Taylor & Francis.